Antimicrobial chemotherapy of patients with lymphadenitis and adenophlegmon of the maxillofacial region - R. V. Ushakov; V. N. Tsarev; A. R. Ushakov; A. A. Labazanov (Эндодонтия Today)
Relevance. Patients with maxillofacial lymphadenitis account for 3.09 % of the total number of hospitalized in specialized departments of maxillofacial surgery, and 5.7% of the number of patients with various inflammatory processes of the maxillofacial region.Aim. Microbiological substantiation of the algorithm of antimicrobial chemotherapy for lymphadenitis and adenophlegmon of the maxillofacial region.Materials and methods. The analysis of the results of microbiological studies and determination of the sensitivity of isolated microorganisms to antibiotics of the material from inflammatory foci in lymphadenitis and adenophlegmon of the maxillofacial region was carried out using a standard protocol of laboratory microbiological studies. Anaerobic bacteria were cultured in the HiAnaerobic System Mark III anaerostat, identification was carried out using Biochemical Identification Test Kits (Himedia Labs).Results. The results of determining the sensitivity of the main pathogens of limphadenitis and adenophlegmon to the most commonly used antibiotics: groups of beta- lactam drugs, macrolides, lincosamides, imidazoles, teracyclines and fluoroquinolones are presented. The priorities of prescribing different treatment regimens are determined, taking into account the international classification of antibiotics AWaRe, adopted by WHO in 2018.Conclusions. Recommended drugs of choice for various forms of lymphadenitis and adenoflegmon include combinations of amoxicillin with clavulanic acid, lincosamides (preferably clindamycin) and fluoroquinolones (ciprofloxacin), which should be combined with imidazoles in odontogenic limphadenitis and adenophlegmon (for example, tinidazole as part of the complex drug Tsifran ST).